New Frontiers in Photochromism - Irie, Masahiro; Yokoyama, Yasushi; Seki, Takahiro; SpringerLink (Online service) (Tokyo : Springer Japan : Imprint: Springer, 2013)
Photochromism is the reversible phototransformation of a chemical species between two forms having different absorption spectra. During the phototransformation not only the absorption spectra but also various physicochemical properties change, such as the refractive index, dielectric constant, oxidation/reduction potential, and geometrical structure. The property changes can be applied to photonic equipment such as erasable memory media, photo-optical switch components, and display devices. This book compiles the accomplishments of the research project titled (3z(BNew Frontiers in Photochromism(3y (Bsupported by the Ministry of Education, Culture, Sports, Science and Technology of Japan. The project focused not only on the above-mentioned classical subjects in photochromism, such as color changes, optical memory, and optical switches, but also on fundamental physicochemical studies and unprecedented application fields that have not yet been explored in photochromism. The latter topics include light-driven mechanical motion, photocontrol of surface wettability, metal deposition on solid materials, photocontrol of chiral properties, ultrafast decoloration dyes, and femtosecond laser experiments, among others.s
New Photochromic Materials -- Photomechanical Response of Diarylethene Single Crystals -- Photomechanical Bending of Molecular Crystals -- Photoinduced Reversible Topographical Changes on Diarylethene Microcrystalline Surface with Wetting Property -- Selective Metal Deposition Based on Photochromism of Diarylethenes -- Photoinduced Alignment and Structuring in Thin Films of Azobenzene-Containing Liquid Crystalline Polymers -- Photochromism of Diarylethenes at Surfaces and Interfaces -- Photo-control of Magnetic Materials Utilizing Photochromic Compounds -- New Photochromic Molecules -- High Performance Thermally Irreversible Photochromism Based on 6(Ss(B-Electrocyclization -- Fast Photochromism of Bridged Imidazole Dimers -- Photochromic Terarylenes -- Photochromic Organometallics: Redox-active Iron and Ruthenium Complexes with Photochromic DTE Ligand -- Ultrafast Dynamics and Mechanism of One-Photon and Multiphoton Photochromic Reactions -- Photochromism of Organic Compounds Undergoing Isomerization Around the C=C Double Bond and/or Intramolecular Hydrogen Atom Transfer: Small and Large Structural Change -- Photo-control of New Molecular Functions by the Isomerization of Azobenzene.s
Keywords: Chemistry; Spectroscopy; Chemistry, Physical organic; Polymers; Optical materials; Chemistry; Physical Chemistry; Optical and Electronic Materials; Polymer Sciences; Spectroscopy/Spectrometry.